Photoacoustic stimulation promotes the osteogenic differentiation of bone mesenchymal stem cells to enhance the repair of bone defect. Issue 1 (December 2017) - Huang, Zebin; Xu, Jiankun; Chen, Jiebin; Chen, Hongjiang; Wang, Hailong; Huang, Zhonglian; Chen, Youbin; Lu, Xiaolin; Lu, Fushen; Hu, Jun
Abstract The aim of this study was to evaluate the direct photoacoustic (PA) effect on bone marrow mesenchymal stem cells (BMSCs) which is a key cell source for osteogenesis. As scaffold is also an indispensable element for tissue regeneration, here we firstly fabricated a composited sheet using polylactic-co-glycolic acid (PLGA) mixing with graphene oxide (GO). BMSCs were seeded on the PLGA-GO sheets and received PA treatmentin vitro for 3, 9 and 15 days, respectively. Then the BMSCs were harvested and subjected to assess alkaline phosphatase (ALP) activity, calcium content and osteopontin (OPN) on 3, 9 and 15 days. Forin vivo study, PLGA-GO sheet seeded with BMSCs afterin vitro PA stimulation for 9 days were implanted to repair the bone defect established in the femoral mid-shaft of Sprague-Dawley rat. PLGA-GO group with PA pretreatment showed promising outcomes in terms of the expression of ALP, OPN, and calcium content, thus enhanced the repair of bone defect. In conclusion, we have developed an alternative approach to enhance the repair of bone defect by making good use of the beneficial effect of PA.